LAYANAN KETATAUSAHAAN DAN SARANA PRASARANA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 LAMBU KABUPATEN BIMA - Sri Asmiatiningsih (Public Service and Governance Journal, 2022)
In order to support the smooth teaching and learning process at the State Junior High School (SMP) 1 Lambu, Bima Regency, a department that supports these activities is needed, namely administration. Administration is a part of the school that functions as a supporter of teaching and learning activities that take place at the Junior High School (SMP) Negeri 1 Lambu, Bima Regency so that it runs smoothly according to what has been planned and can be achieved as desired. With the development of the era which is now better known as the era of globalization, the administrative function must be able to improve its quality regarding technology, especially information technology or better known as the computerized era.